Optimal Location of Landfill in Semirom County Using the Combination of Fuzzy Logic (AND, OR algorithm) in GIS - Sohrab Hasheminejad; Samane Shahrabi Farahani; Reza Peykanpour Fard (اکولوژی انسانی)
Despite efforts to reduce reliance on landfilling, sanitary landfilling remains a significant waste management method in many cities, albeit with inherent environmental limitations. A major challenge, particularly in developing cities, is the scarcity of suitable landfill sites that meet stringent environmental regulations. Selecting a suitable landfill site necessitates a comprehensive evaluation of relevant criteria, including environmental, geographical, and socioeconomic factors. This study determined the most suitable sanitary landfill site using a multi-criteria decision analysis based on proximity to urban and rural centers, protected areas, and water bodies; distance from major roadways; slope; and proximity to wells. Optimal areas were identified using fuzzy logic within a GIS environment, integrating criteria maps. Spatial overlays incorporating minimum (Min) and maximum (Max) functions, representing fuzzy AND and OR operations respectively, were employed to delineate suitable and unsuitable areas based on the predefined criteria. The comparative analysis of results obtained using the fuzzy AND (Min) and OR (Max) functions revealed that the AND (Min) function yielded a more environmentally sound selection of potential landfill sites, as it minimized conflict with sensitive environmental features, such as protected areas and water bodies. This approach prioritized sites that met all criteria to a satisfactory degree, rather than those meeting just some.